EFFECT OF ELECTRIC FIELD STRENGTH ON SURFACE LAYER DESTRUCTION IN INSULATION CONSTRUCTION - Y.G. Gontar (National Technical University "Kharkiv Polytechnic Institute", 2013)
Results of theoretical and experimental studies of surface layer destruction in electrical insulation under lightning surge pulses are given, their impact on the insulation construction durability shown. Causes of water treeing in the surface layers of polymer insulation are analyzed.